Development and Productivity Waqf in Sharia Insurance in Indonesia and Egypt: A Comparative Analysis - Suhada Setiawan; Muhammad Bagus Saputro; Mufti Afif; Khurun’in Zahro (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
Professional management of waqf funds will facilitate its growth and development. This article aims to shed light on the development and potential of Islamic insurance waqf in Indonesia, with a view to increasing its productivity and scope of development. Following the issuance of the DSN-MUI fatwa in 2016, which addresses the issue of Waqf of Insurance Benefits and Waqf of Investment Benefits on the subject of sharia-compliant life insurance, Indonesia can benefit from the examples provided by countries in the Middle East, such as Egypt, which has long been a pioneer in the development of its waqf, which has become a permanent provision in Egyptian law. This research utilises a qualitative descriptive research design. The data collected is analysed by providing a comprehensive picture of the development of Islamic insurance waqf. The findings of this study indicate that the development of Islamic insurance waqf is positive and has significant potential in the future. This is due to the large Muslim population in Indonesia, which provides a great opportunity for the growth of this form of Islamic finance. Provided that the conceptual and concrete barriers that may hinder its development can be effectively addressed by the relevant authorities and the general public, its growth potential is quite significant.